HGF-MET Signaling Shifts M1 Macrophages Toward an M2-Like Phenotype Through PI3K-Mediated Induction of Arginase-1 Expression - Nishikoba, Nao; Kumagai, Kotaro; Kanmura, Shuji; Nakamura, Yuko; Ono, Mayumi; Eguchi, Hiromi; Kamibayashiyama, Tomomi; Oda, Kohei; Mawatari, Seiichi; Tanoue, Shiroh; Hashimoto, Shinichi; Tsubouchi, Hirohito; et al. (Frontiers in Immunology, 2020)
Backgrounds and Aims: Hepatocyte Growth Factor (HGF)-MET signaling is known to promote biological functions such as cell survival, cell motility, and cell proliferation. However, it is unknown if HGF-MET alters the macrophage phenotype. In this study, we aimed to study the effects of HGF-MET signaling on the M1 macrophage phenotype. Methods and Materials: Bone marrow-derived macrophages (BMDMs) isolated from mice were either polarized to an M1 phenotype by IFN-and LPS treatment or to an M2 phenotype by IL-4 treatment. Changes in M1 or M2 markers induced by HGF-MET signaling were evaluated. Mechanisms responsible for alternations in the macrophage phenotype and intracellular metabolism were analyzed. Results: c-Met was expressed especially in M1 macrophages polarized by treatment with IFN- and LPS. In M1 macrophages, HGF-MET signaling induced the expression of Arg-1 mRNA and secretion of IL-10 and TGF-1 and downregulated the mRNA expression of iNOS, TNF-, and IL-6. In addition, activation of the PI3K pathway and inactivation of NFB were also observed in M1 macrophages treated with HGF. The increased Arg-1 expression and IL-10 secretion were abrogated by PI3K inhibition, whereas no changes were observed in TNF- and IL-6 expression. The inactivation of NFB was found to be independent of the PI3K pathway. HGF-MET signaling shifted the M1 macrophages to an M2-like phenotype, mainly through PI3K-mediated induction of Arg-1 expression. Finally, HGF-MET signaling also shifted the M1 macrophage intracellular metabolism towards an M2 phenotype, especially with respect to fatty acid metabolism. Conclusion: Our results suggested that HGF treatment not only promotes regeneration in epithelial cells, but also leads to tissue repair by altering M1 macrophages to an M2-like phenotype.